Crisis States: Governance, Resistance & Precarious Capitalism - Shantz, Jeff (punctum books, 2016)
This is an age of crisis: economic, political, environmental, and social. Yet the nature of contemporary crisis is often misunderstood. Crisis, rather than being accidental or episodic - as is too often assumed - has been a regular feature of state practice in the neoliberal austerity regimes of contemporary capitalism. In this timely work Jeff Shantz gives special attention to the particular manufactured crises associated with austerity regimes and conditions of precarity within contemporary capitalism, and how Crisis States differ from other forms of state practice. Crisis is a powerful weapon of states and capital in the pursuit of accumulation, exploitation, and control. Engaging insights from anarchism and autonomous Marxism, Shantz lays bare the real nature and character of crisis as political and social pursuits of state and capital under precarious capitalism. Attention is also given to social resistance under crisis state conditions. Contemporary capitalism renders the oppressed and exploited precarious at the same time as opportunities are opened to render the system itself precarious. Understanding Crisis States and precarious capitalism is crucial in considering prospects for resistance.